A case of refractory systemic lupus erythematosus with monocytosis exhibiting somatic KRAS mutation - Sze-Ming Law; Shuji Akizuki; Akio Morinobu; Koichiro Ohmura (BMC, 2022)
Abstract Background Systemic lupus erythematosus (SLE), an autoimmune disorder that damages various organ systems, is caused by a combination of genetic and environmental factors. Although germline mutations of several genes are known to cause juvenile SLE, most of the susceptibility genetic variants of adult SLE are common variants of the population, somatic mutations that cause or exacerbate SLE have not been reported. We hereby report a refractory SLE case with monocytosis accompanying somatic KRAS mutation that have been shown to cause lupus-like symptoms. Case presentation A 60-year-old female patient who had been diagnosed with SLE was admitted to our hospital. Although prednisolone and tacrolimus treatments had kept her thrombocytopenia and anti-DNA Ab level at bay for more than 4 years, a diagnosis of transverse myelitis was made when she became acutely ill with pleocytosis. Elevated cells (predominately monocytes), protein, IgG, and IL-6 levels were also found in the cerebrospinal fluid (CSF) of the patient. Standard pulse treatments of methylprednisolone, high-dose of prednisolone, and intravenous cyclophosphamide in combination with plasma exchange could not alleviate the refractory neural and autoimmune manifestation. Monocytosis of peripheral blood was also noted. Flow cytometric analysis revealed elevated ratio of CD14+CD16+ atypical monocytes, which excluded the possibility of chronic myelomonocytic leukemia. Lupus-like symptoms with monocytosis reminded us of Ras-associated autoimmune leukoproliferative disorder, and Sanger sequencing of KRAS and NRAS genes from the patients' peripheral blood mononuclear cells (PBMC), sorted CD3+ lymphocytes and CD14+ monocytes, and cerebrospinal fluid were performed. An activating KRAS somatic mutation was found in the patients' DNA at the time of encephalomyelitis diagnosis. Conclusion Somatic mutations of some genes including KRAS may cause the refractoriness of SLE.